Defending diversity : affirmative action at the University of Michigan - Gurin, Patricia (University of Michigan Press ; University Presses Marketing, distributor], 2004)
"Even as lawsuits challenging its admissions policies made their way through the courts, the University of Michigan carried the torch for affirmative action in higher education." "The University's position on affirmative action was vindicated in June 2003, when the Supreme Court ruled that race may be used as a factor in university admissions programs. The Court thus upheld what the University had argued all along: diversity in the classroom translates to a beneficial and wide-ranging social value. With the green light given to the University's law school admissions policies, Defending Diversity validates the positive benefits gained by students in a diverse educational setting.".